1943
DOI: 10.1001/jama.1943.02840070029009
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ascorbic Acid in Relation to Lead Absorption

Abstract: reported a case, with similar symptoms to ours, responding favorably to orchiectomy: A man aged 71 had abdominal and low back pain, numbness over the buttocks and posterior part of the thighs as well as urinary and fecal inconti¬ nence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1948
1948
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Back in 1940 Dannenberg et al described an unsuccessful attempt to treat with ascorbic acid a 27-month-old child suffering from lead encephalopathy. Studies in lead-exposed workers did not show beneficial effect of ascorbic acid on blood lead concentration, lead elimination and/or biochemical markers of lead toxicity (Evans et al 1943;Lauwerys et al 1983). Dietary ascorbic acid supplementation also did Author for correspondence: Veda M. Varnai, Institute for Medical Research and Occupational Health, P.O.…”
mentioning
confidence: 99%
“…Back in 1940 Dannenberg et al described an unsuccessful attempt to treat with ascorbic acid a 27-month-old child suffering from lead encephalopathy. Studies in lead-exposed workers did not show beneficial effect of ascorbic acid on blood lead concentration, lead elimination and/or biochemical markers of lead toxicity (Evans et al 1943;Lauwerys et al 1983). Dietary ascorbic acid supplementation also did Author for correspondence: Veda M. Varnai, Institute for Medical Research and Occupational Health, P.O.…”
mentioning
confidence: 99%
“…HoImes et al (1939 provided evidence for reduced severity of lead toxicity in metal workers after ascorbic acid therapy. but this was not the case for workers in a tetraethyl lead plant (Evans et al 1943). These contradictory findings may be a result of an improvement in overall health of lead-poisoned patients, previously having a poor diet, as we11 as a lead-chelating action of ascorbic acid similar to that of EDTA (ethylenzdiaminetetraacetic acid) (Goycr and Chcrian 1978).…”
Section: Resultsmentioning
confidence: 98%
“…Pillemer and coworkers (30) found that lead poisoned guinea pigs on a scorbutic diet developed neurological symptoms more readily than did lead poisoned animals fed ascorbic acid adequate diets. Other investigators, however, have found ascorbic acid to be without effect in lead toxicity (31,32).…”
Section: Toxic Effects Of Leadmentioning
confidence: 88%